Facilitating children's learning in the EYFS - Langston, Ann (Supporting learning in the EYFS, 2013)
This book will address a range of issues pertinent and prominent in the revised EYFS including brain development; school readiness; engaging parents; and the rationale behind the new prime and specific areas of learning.